A micro-patterned electrode/electrolyte interface fabricated by soft-lithography for facile oxygen reduction in solid oxide fuel cells. Issue 32 (3rd August 2020) - Lee, Channyung; Shin, Sung Soo; Choi, Jiwoo; Kim, Jinhyeon; Son, Ji-Won; Choi, Mansoo; Shin, Hyun Ho
Abstract : The performance of solid oxide fuel cells can be improved by introducing micro-patterns on their electrolyte layer. Abstract : The performance of solid oxide fuel cells can be improved by introducing micro-patterns on their electrolyte layer. However, because of the undesired properties of ceramic structures, the application of patterning has been limited to a few electrolyte-supported cells with thick electrolyte layers and requires expensive energy-consuming tools. Herein, we report an advanced micro-patterning technique that can be applied to the thin electrolyte of tape-cast anode-supported SOFCs. By employing soft-lithography with a UV curable electrolyte slurry, we fabricated regularly ordered micro-patterns on a thin electrolyte layer, while maximizing the interface area between the cathode and the electrolyte. Electrochemical impedance spectroscopy measurements followed by the distribution of relaxation time analysis revealed that with the increase in the triple phase boundary near the patterned interface area, the polarization resistance significantly decreases owing to the facilitated oxygen reduction reactions at the cathode, resulting in a significant improvement in the cell performance. The microstructure and morphology of the patterned cells were investigated by scanning electron microscopy and atomic force microscopy. The results confirm the feasibility of the facile micro-patterning method in engineering the surfaces of ceramic-based layered electrochemical devices with dramatically improved performance due to enhanced electrochemical reactions.